Recession managers and mutual fund performance - Chen, Jie; Lasfer, Meziane; Song, Wei; Zhou, Si (Journal of Corporate Finance, 2021)
We find that fund managers who began their careers during recessions produce superior returns. This superior performance is not unconditional, as they exhibit better market timing than their non-recession counterparts in recessions, but do not demonstrate better stock picking in booms. Exploring managers' portfolio choices across years, we find that recession managers tilt their investments towards defensive, rather than cyclical, industries during and before recession periods. Overall, our findings support the argument that the economic conditions under which an individual initially entered the labour market exert a long-term impact on her career outcomes and decision-making.